Design and Validation of an Observational Instrument for the Technical-Tactical Actions in Singles Tennis - Torres-Luque, Gema; Fernández-García, Ángel Iván; Cabello-Manrique, David; Giménez-Egido, José María; Ortega-Toro, Enrique (Frontiers in Psychology, 2018)
The competitive performance in tennis practice is determined by the effectiveness of technical tactical action. The main objective of the present study was to design and validate an observational instrument with the aim of analysing the technical-tactical in singles tennis. The instrument uses the stroke as a unit of measure, so that each time a player hits a ball, a total of 23 variables are analyzed. The variables collect information about: (a) matching context; (b) result; and (c) technical-tactical information of the stroke (five variables: sequences of the stroke of the point, kind of technical and tactical stroke, bounce area, hitting, and effectiveness area). The design and validation of the instrument consisted on five different stages: (a) review of the scientific literature and variables definition by experts, (b) pilot observation study, (c) qualitative and quantitative assessment of the instrument by experts, (d) review and confirmation of the instrument by experts (content validity), and (e) observation training and reliability evaluation. From 23 expert judges, divided into three panels, and four observers the instrument went from being composed of 38 variables (eight contextual, seven related to the result and 23 related to the game) to 23 (eight contextual variables, 10 of result and five of game), with minimum Aikens's V values of 0.94 and reliability of 0.81. The results show that the designed instrument allows obtaining valid and objective information about the technical-tactical actions of the players and their performance in singles tennis